The Impact of Waiting Time on Patient Satisfaction with Laboratory Samples Collection in Sheikh Khalifa Medical City, United Arab Emirates - Almessabi, Naof; Alshamsi, Saud (Global Journal of Health Sciences, 2025)
Purpose: The IOM has introduced the 6 fundamental aims, patient-centred and timely. Patients’ satisfaction is their reactions to aspects that have a previous expectation, and the importance of patient satisfaction influences the clinical outcomes. The aim is to demonstrate the effects of waiting time on patients’ satisfaction with laboratory sample collections. Methodology: A quantitative cross-sectional design, implemented in SKMC, Abu Dhabi, UAE. Participants are from outpatient clinics, both genders and from the age of 18. Simple random sampling has been chosen to reduce bias errors and provide a chance to all individuals equally for participation. Using Microsoft Forms to initiate the survey with a total of 7 questions translated into Arabic and English languages. Findings: The total number of participants was 228, 66% of them chose the Arabic language to answer the survey’s question whereas 34% proceeded with the English language. The majority age group of our respondents was from 20 to 30 years old at 46.5%, and the lowest age group participated are from the age of 61 and above with 1.3%. Most of the participants were satisfied with lab registration members (85.1%), satisfied with waiting times (70%), satisfied with staff attitudes (84.2%), satisfied with cleanliness (89.5%), satisfied with instruction (94.7%), satisfied with overall experience (85.1%). Unique Contribution to Theory, Practice and Policy: To end up, this research has successfully clarified the positive significance relationship between waiting time satisfaction and overall experience satisfaction. Current research highlights the impact of waiting time satisfaction on overall experience satisfaction. It focused on the priority of maintaining patient flow along with managing time. This finding suggests that improving patient waiting time enhances the overall experience. Future recommendations include precision of the measurements for waiting time, including demographic variables, and collecting qualitative data for more insights.